Escaping the self-determination trap - Weller, M. (Marc) (Martinus Nijhoff, 2008)
There is a movement in the discussion about self-determination and statehood. This monograph argues that classical self-determination, narrowly conceived in the colonial context, cannot contribute to the resolution of the self-determination conflicts. It finds that a fresh practice of addressing self-determination conflicts has emerged.